Penyusunan Sistem Pengelolaan Kearsipan Digital Berbasis Microsoft Access Pada Bagian Sertifikasi PT Insurin Balikpapan - Alisa Alaina; Isti Prabawani; Ode Merlim (Jurnal Mahasiswa Kreatif, 2023)
In the archive management system in a company, it is necessary to renew the archive management so that the records can be managed properly. The problem in this study is that the archive management system at the PT INSURIN Balikpapan Certification section can still be said to be less than optimal, due to the lack of knowledge about archive management and also a lack of awareness of the importance of archives. This study aims to develop a digital archive management system that can facilitate the search for archival data that is safe, fast, accurate, and more efficient. In this study, the type of research used was descriptive research with a qualitative approach using descriptive data analysis. The data collection techniques used are observation, interviews, and documentation, and use of seven other stages in the preparation of the system, namely the planning stage, the implementation stage, the testing stage, the analysis stage, the feedback stage, the repair stage, and the validation stage. The data analysis technique is through data reduction, data presentation, and conclusion drawing. Based on the research conducted, it can be concluded that the preparation of the application program that has been compiled can be used in archival management activities at the PT INSURIN Certification section to replace the previous system because it is considered effective but still requires the addition of other menus, especially in terms of archive search. It still needs development with the addition of other menus considering the many tools offered in the Microsoft Access application so that the system becomes more innovative, as well as renewal of archival equipment in the form of a roller-type scanner so that the process of scanning reports can be more practical and effective.